The current research status of normal tension glaucoma - Xue-Song Mi, Xuesong; Yuan, Ti-Fei; So, Kwok-Fai (Clinical interventions in aging, 2014)
Normal tension glaucoma (NTG) is a progressive optic neuropathy that mimics primary open-angle glaucoma, but lacks the findings of elevated intraocular pressure or other mitigating factors that can lead to optic neuropathy. The present review summarized the causes, genetics, and mechanisms underlying NTG in both animal models and human patients. We also proposed that the neurovascular unit is a therapeutic target for NTG management.